Extent of road lighting impact on the quality of roadway service - Kurnia, Aztri Yuli (2012)
The quality of road surface and its facility will relate to performance evaluation, which relies on measures of performance quality, often stated in quality of roadway service (QRS). One of the facilities that available in highway outside the carriageway is road furniture, including road lighting. The availability of road lighting in highway helps driver at night time driving. Road lighting be expected can make road can be functioned in night time as well as drive in daytime. This study will compare QRS of two scenarios – day light condition and road light condition – in dry weather. QRS can be estimated by comparing 85th and 15th percentiles of cumulative speed distribution. Roadway capacity during daylight is estimated approximately 2096 pcu/hr/ln, while during road lighting the roadway capacity is 2154 pcu/hr/ln. The 15th percentile speed during day light is 61 km/hr, decreasing to 59 km/hr during road lighting condition. The 85th percentile speed during day light and road lighting are 88 km/hr and 85 km/hr respectively. Statistical test result shown that the difference of 85th and 15th percentile speed during day light and road lighting condition was statistically not significant. Optimum speed during daylight is 46.17 km/hr, while during road lighting is decrease to 44.42 km/hr. Since speed is a distributed parameter, a variance within 32.67 km/hr to 59.67 km/hr for the speed can be neglected and QRS assumed not affected. It shows that QRS under proper standard lighting system is not affected significantly compare to the daylight condition.